2021
DOI: 10.1523/jneurosci.0819-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Fluorescence Lifetime Imaging Reveals That TRPV4 Channels Promote Dysregulation of Neuronal Na+in Ischemia

Abstract: Fluorescence imaging is an indispensable method for analysis of diverse cellular and molecular processes, enabling, for example, detection of ions, second messengers, or metabolites. Intensity-based approaches, however, are prone to artifacts introduced by changes in fluorophore concentrations. This drawback can be overcome by fluorescence lifetime imaging (FLIM) based on time-correlated single-photon counting. FLIM often necessitates long photon collection times, resulting in strong temporal binning of dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…Various pathways have been proposed and observed to account for the movement of water into and out of neurons, as neuronal size regulation is essential for their survival. Some of these pathways involve CCCs, VRACs, monocarboxylate transporters, potassium channels, Na + /H + exchangers, voltage-gated chloride channels, SLC26A11, TRPV4 ( Hellas and Andrew, 2021 ; Meyer et al, 2021 ; Pasantes-Morales, 2016 ; Rungta et al, 2015 ; Wilson and Mongin, 2018 ). Importantly, in neurons, the movement of ions is intimately linked to that of water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various pathways have been proposed and observed to account for the movement of water into and out of neurons, as neuronal size regulation is essential for their survival. Some of these pathways involve CCCs, VRACs, monocarboxylate transporters, potassium channels, Na + /H + exchangers, voltage-gated chloride channels, SLC26A11, TRPV4 ( Hellas and Andrew, 2021 ; Meyer et al, 2021 ; Pasantes-Morales, 2016 ; Rungta et al, 2015 ; Wilson and Mongin, 2018 ). Importantly, in neurons, the movement of ions is intimately linked to that of water.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in juvenile and adult brain slices have shown that hypoxia induces astrocytic and neuronal swelling ( Hellas and Andrew, 2021 ; Meyer et al, 2021 ; Risher et al, 2009 ). Neuronal cytotoxic edema results from an influx of ions, primarily Na + and Cl − , accompanied by water, from the interstitial space into the intracellular compartment ( Glykys et al, 2017 ; Halstead and Geocadin, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prominent pathways for Na + influx into neurons are NMDA receptors, while in astrocytes, Na + ‐dependent glutamate transporters are predominant Na + loaders (Gerkau et al., 2018; Rungta et al., 2015; Song et al., 2020). In addition to these well‐established mechanisms, transient receptor potential vanilloid 4 (TRPV4) channels were recently shown to mediate Na + influx into neurons under ischemic conditions (Meyer, Gerkau et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…TRPV4 channels are osmotically regulated unspecific cation channels that are activated in the ischemic penumbra and are expressed by neurons and astrocytes (Rakers et al., 2017; Yu et al., 2019). The contribution of TRPV4 to neuronal Na + loading in ischemic conditions (Meyer, Gerkau et al., 2022) suggests that their activation might also promote the loss of cellular ATP in ischemic conditions in both cell types. To address this question, we employed fluorescence‐based imaging of ATP with the nanosensor ATeam1.03 YEMK expressed in neurons or astrocytes in organotypic tissue slices of the mouse neocortex.…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytic TRPV4 has been shown to be involved in a couple of Ca 2+ activated processes of the ischemic cascade–excitotoxicity [ 15 , 169 ], peri-infarct depolarization [ 170 ], oxidative stress [ 6 ] or astrocytic swelling [ 113 , 118 ].…”
Section: Trpv4 Channels In Glial Cellsmentioning
confidence: 99%